Evaluation of the Regression Coefficient between the Activity of FoxP3 Gene on Regulatory T Cells and Glucose Level in Patients with type 1 Diabetes Mellitus In the City of Mosul (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Still, external insulin therapy with its various types causes a variety of immune reactions through its variable control of the glucose level in patients with type 1 diabetes. However, major immune problems are uncommon, and less serious diabetic events have long-term effects on immune responses. The current study aimed to follow up the effect of glucose levels on the level of gene expression of the FoxP3 gene, one of the most important genes responsible for the activity of Regulatory T cells in patients with type 1 diabetes. (26) blood samples were collected from individuals diagnosed with type 1 diabetes for a period of more than (5) years, their ages ranged from (15-35) years, and from both sexes, from Al-Wafa Center for the treatment of diabetics and endocrine glands in the city of Mosul. The patients were divided into four groups, depending on the type of insulin injection , These groups included (Actrapid patients group, Insulatard patients group, Insulatard / Actrapid patients patients group, and finally Mixtard patients group). The control group also included (7) blood samples of healthy people as donors, ages ranging from (15-30) years, (males and females), without communicable diseases, bacterial infections, or autoimmune diseases. . The results showed an effect of glucose concentration on the expression level of the FoxP3 gene by (26%) in the group of patients who used insulin mixtard type, while the results of the effect analysis of glucose on the level of gene expression of the FoxP3 gene showed a rate of (76%) in the group of patients who used insulin type Insulatard, On the contrary, there was no effect of glucose concentration on the level of FoxP3 gene expression in patients using Actrapid and  Insulatard / Actrapid insulin at (P≤0.05).